Modeling Outcomes Using Sequential Organ Failure Assessment (SOFA) Score-Based Ventilator Triage Guidelines During the COVID-19 Pandemic. (14th February 2023) - Cuartas, Pablo Alberto; Tavares Santos, Heitor; Levy, Benjamin M; Gong, Michelle Ng; Powell, Tia; Chuang, Elizabeth
Abstract: Objective: To model performance of the Sequential Organ Failure Assessment (SOFA) score-based ventilator allocation guidelines during the COVID-19 pandemic. Methods: A retrospective cohort study design was used. Study sites included 3 New York City hospitals in a single academic medical center. We included a random sample (205) of adult patients who were intubated (1002) from March 25, 2020, till April 29, 2020. Protocol criteria adapted from the New York State's 2015 guidelines were applied to determine which patients would have had mechanical ventilation withheld or withdrawn. Results: 117 (57%) patients would have been identified for ventilator withdrawal or withholding based on the triage guidelines. Of those 117 patients, 28 (24%) survived hospitalization. Overall, 65 (32%) patients survived to discharge. Conclusion: Triage protocols aim to maximize survival by redirecting ventilators to those most likely to survive. Over 50% of this sample would have been identified as candidates for ventilator exclusion. Clinical judgment would therefore still be needed in ventilator reallocation, thus re-introducing bias and moral distress. This data suggests limited utility for SOFA score-based ventilator rationing. It raises the question of whether there is sufficient ethical justification to impose a life-ending decision based on a SOFA scoring method on some patients in order to offer potential benefit to a modest number of others.